Analysis of the Alignment of the Fiqh Teaching Module with 21st-Century Skills - Yemmardotillah, M.; Indriani, Rini; Pismawenzi, Pismawenzi; Darlis, Ahmad (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2024)
Teaching modules are instructional tools containing lesson plans that guide the learning process to achieve specific Learning Outcomes. This research aims to evaluate the alignment of fiqh teaching modules with 21st-century skills. The research uses a qualitative method with a case study approach, and data were obtained from Islamic Senior High School fiqh teaching modules. Data analysis involved qualitative techniques, including data reduction, data presentation, and conclusion drawing. Findings show that the fiqh teaching module integrates 21st-century skills, specifically character education, Higher-Order Thinking Skills (HOTS) , literacy, and 4C (critical thinking, creativity, communication, and collaboration). Character education includes values like religiosity, independence, cooperation, nationalism, and integrity. HOTS is embedded through operational verbs such as analyze, evaluate, and compare in lesson planning and assessments. Literacy components encompass basic, media, technological, and visual literacies, while the 4C are demonstrated through discussions, presentations, and group activities.